ANALISIS HUBUNGAN DISPOSISI MATEMATIKA SISWA TERHADAP KEMAMPUAN KONEKSI MATEMATIKA SELAMA PANDEMI COVID-19 DI SMK N 1 SOSORGADONG - Misbatul Khairah Pohan; Muhammad Syahril Harahap; Eva Yanti Siregar (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2022)
Abstract This research was motivated by the presence of COVID-19 at the beginning of 2020 which had a tremendous impact on almost all fields, one of which was in the field of education. Based on this situation, the researcher is interested in describing the Analysis of the Relationship between Students' Mathematical Dispositions on Mathematical Connection Ability During the Covid-19 Pandemic at SMK N 1 Sosorgadong. The research method used in this study is descriptive research and the subjects in this study were class X students of SMK Negeri 1 Sososrgadong, questionnaires and mathematical connection test sheets were used to collect data. The results of the test data about students' mathematical connection abilities in class X-TKJ II of SMK Negeri 1 Sosorgadong included the